STUDENT’S ABILITY TO FORMULATE RESEARCH QUESTIONS: A STUDY OF INITIAL RESEARCH PROCESS IN PROPOSAL WRITING AT ENGLISH TEACHER EDUCATION DEPARTMENT - Azami, Mochamad Imron (IJET (Indonesian Journal of English Teaching), 2016)
The purpose of this study is to know the students’ process in formulating research question in writing 4 (proposal) and also to know their reason why they choose that steps in formulating research question. This study used qualitative design and chooses descriptive methods to describe the data in this study. The researcher used interview guidelines gained the data through semi structured interview. This study used all of students in English Teacher Education Department in academic years 2012. The numbers of students in this study are 80 students. After gained the data from interview, the researcher used coding to classify the data, then used theory to assess whether the students’ process in formulating research question is appropriate with the theory or not. The result shows that there are 7 types in formulating research question (from title, problem, journal, thesis, issue, topic and consulting to their lecturer). From each type, the researchers conclude that there was some students just follow 1 step in good process of formulating research question. There was one student just follow the first step (choose an interesting topic) in formulating research question. The others, just follow the second step (Do some preliminary research in your general topic). There was no student used all of good process in formulating research question. So the researchers conclude that there was no students at English Teacher Education Department Students follow good process in formulating research question.